Maternal investment decreases under stressful environments in 11 plateau brown frog (Rana kukunoris) populations. Issue 2 (4th March 2018) - Yu, Tong Lei; Xu, Yu; Busam, Michael; Deng, Yao Hui
Abstract : Environmental pressures vary by geographic location and will lead to differentiation in life history traits according to which maximize fitness. Life history theory predicts that harsh environments are likely to select for larger egg or offspring size, and for a stronger trade-off between offspring size and number. To test this prediction, we compared life history traits among 11 plateau brown frog ( Rana kukunoris ) populations at different altitudes. We found that females with a concomitant increase in body size produce larger eggs and more offspring in warm environments than females in cold environments do. Moreover, females from two natural populations produced offspring of different sizes between years. The decreasing resource allocation to current offspring size and number may increase survival and future fecundity in harsh environments. Thus, there may be a trade-off between mortality and fecundity in different environments. In addition to body size, we suggest that temperature plays an important role in shaping maternal investment variation in R. kukunoris across geographical gradients.